2013
DOI: 10.3389/fnhum.2013.00425
|View full text |Cite
|
Sign up to set email alerts
|

The effects of breakfast on behavior and academic performance in children and adolescents

Abstract: Breakfast consumption is associated with positive outcomes for diet quality, micronutrient intake, weight status and lifestyle factors. Breakfast has been suggested to positively affect learning in children in terms of behavior, cognitive, and school performance. However, these assertions are largely based on evidence which demonstrates acute effects of breakfast on cognitive performance. Less research which examines the effects of breakfast on the ecologically valid outcomes of academic performance or in-clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
226
4
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(256 citation statements)
references
References 79 publications
15
226
4
11
Order By: Relevance
“…Studies have demonstrated that regular breakfast enhances cognitive performance in children; memory and attention in particular [8,9,16]. Although trail making performance was slightly better in the group who had breakfast in our study, they were not significantly different from the students who did not have breakfast on the day of interview.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Studies have demonstrated that regular breakfast enhances cognitive performance in children; memory and attention in particular [8,9,16]. Although trail making performance was slightly better in the group who had breakfast in our study, they were not significantly different from the students who did not have breakfast on the day of interview.…”
Section: Discussioncontrasting
confidence: 84%
“…Some studies have reported that there aren't any significant effects on cognitive functions [6,7]. Further, not many studies have shown that skipping breakfast affects tasks requiring attention and concentration [8,9]. Differences in study design, type of sample population, cognitive function assessment procedures might have contributed to these inconsistencies seen in these reports.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that the results of these studies were diverse, breakfast intake seems to have a positive short-term effect on intellectual and cognitive performance as compared to breakfast omission in children and adolescents [2].…”
Section: Introductionmentioning
confidence: 94%
“…Brain function is sensitive to short-term variations in nutrient supply, with several studies examining the immediate (short-term) effects of breakfast on academic performance [2,3]. However, research investigating the long-term effects of breakfast in this regard is less common in the literature [4].…”
Section: Introductionmentioning
confidence: 99%
“…Further, to maintain their higher metabolic rate, children require a continuous supply of energy derived from glucose [2]. However, water and energy are not the only dietary components that play a role; in addition to carbohydrates, fruits and vegetables contain vitamins, minerals and other bioactive substances, which are also important for intellectual performance.…”
Section: Introductionmentioning
confidence: 99%